Merangkai Kenangan, Menemukan Makna: Program Reminiscence Therapy Dalam Menurunkan Tingkat Kesepian Pada Lansia Di Panti Sosial Belas Kasih - Fitratul Muthahharah; Diah Karmiyati; Siti Maimunah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Older adults are a population group that experiences various declines in physical, cognitive, and psychosocial functions, which may increase vulnerability to psychological problems, one of which is loneliness. Loneliness among older adults can have negative effects on mental health, quality of life, and the ability to adapt to the social environment, particularly for those living in residential care facilities. One intervention that may reduce loneliness is reminiscence therapy, a therapeutic approach that encourages individuals to recall and reflect on meaningful life experiences. This study aimed to examine the effectiveness of reminiscence therapy in reducing loneliness among older adults at elderly care home-Panti Sosial Belas Kasih. This study employed a quantitative method with a pre-experimental one-group pretest–posttest design. Levels of loneliness were measured before and after the implementation of reminiscence therapy using the UCLA Loneliness Scale. The sampling technique used was purposive sampling, involving 12 older adults as participants. Data were analyzed using a paired sample t-test to determine differences in loneliness levels before and after the intervention. The results indicated a significant reduction in loneliness following the implementation of reminiscence therapy, with a p-value < 0.001 (α < 0.05). These findings demonstrate that reminiscence therapy is effective in reducing loneliness among older adults at elderly care home-Panti Sosial Belas Kasih. Therefore, reminiscence therapy can be recommended as a psychosocial intervention that is practical and easy to implement to enhance the psychological well-being of older adults.